Fire risk assessment and educational intervention in operating room personnel: An intervention study in Isfahan Hospitals - Mohammadreaz Alizade; Ahmad Ghadami; Zahra Heidari; Mahdi Jalali; Ehsanollah Habibi (International Journal of Environmental Health Engineering, 2023)
Aim: The purpose of this investigation was to evaluate the impact of educational intervention on operating room personnel's knowledge of fire factors and lowering the level of fire risk in some selected hospitals in Isfahan city. Materials and Methods: This interventional study was conducted on 113 operating room personnel of Isfahan hospitals in Iran. A standard questionnaire (with 28 questions) was employed to assess the level of knowledge of the operating room personnel about the sources of combustion and ways to prevent it. The fire risk assessment method for engineering was employed to assess the fire risk of hospitals, and the risk level was calculated for the building and its contents (R), personnel (R1), and activity risk (R2). SPSS version 24 was used to analyze the data. Results: Forty-eight participants (36.1%) were men, and 85 participants (63.9%) were women. The findings demonstrated that the mean (standard deviation) score of personnel's fire safety knowledge was statistically enhanced before and after the educational intervention (10.62 [3.20] and 15.40 [2.66], respectively (P < 00.01). The findings of the fire risk assessment demonstrated that the risk of personnel has the maximum risk score, which is higher than one in all instances. Following personnel risk, the building and its contents risk had the maximum overall risk score. Following the educational intervention, the findings of the fire risk assessment demonstrated that the overall risk of the building and its contents, the overall risk of personnel, and the overall risk of the activity all reduced from 0.588–0.423, 4.174–3.408, to 0.543–0.498, respectively. Conclusion: Proper implementation of educational programs can reduce fire risk while also enhancing personnel knowledge and improving operating room safety. Accordingly, hospitals should incorporate the implementation of educational programs into their routine activities.